Are auditors attenuate earnings management in private companies? The effect of economic adjustment programmes - Dias, P. (2018)
This study analyses the relationship between the level of earnings management and the audit of unlisted companies in two countries liable to economic adjustment programmes - Portugal and Ireland - between 2008 and 2016. The choice of these two countries lies in the fact that they both experienced strong financial assistance programmes, and it is pertinent to assess the indebtedness and earnings management phenomenon in this particular economic harsh context. In a sample of 970 unlisted companies, we find evidence of a negative relationship between the audit and the level of earnings management. We also demonstrate that during the period of time in which the financial support occurred, there was mitigation in the relationship between the level of earnings management and audit.